Seasonal variation in blood pressure: what is still missing? - Barbosa, Eduardo Costa Duarte; Farina, Giovani Schulte; Basso, Carolina Souza; Camafort, Miguel; Coca, Antonio; Nadruz, Wilson (Frontiers in Cardiovascular Medicine, 2023)
Seasonal variation of blood pressure (BP) is a topic in cardiology that has gained more attention throughout the years. Although it is extensively documented that BP increases in seasons coupled with lower temperatures, there are still many gaps in this knowledge field that need to be explored. Notably, seasonal variation of BP phenotypes, such as masked and white coat hypertension, and the impact of air pollution, latitude, and altitude on seasonal variation of BP are still poorly described in the literature, and the levels of the existing evidence are low. Therefore, further investigations on these topics are needed to provide robust evidence that can be used in clinical practice.